Women's language : an analysis of style and expression in letters before 1800 - Haettner Aurelius, Eva, 1948-; Gunneng, Hedda; Helgason, Jon, 1971- (Nordic Academic Press, 2012)
By linguistic close-reading of more than a thousand letters from the 12th through the 18th centurieswritten in Latin, Swedish, French, German, and Englishthis compilation analyzes the differences in language and communication between women and men. Armed with an exhaustive stylistic analysis, this volume attempts to answer the question Is there a special niche reserved for women's language? As it pinpoints the variations in how women expressed themselves when addressing men or other women, this detailed investigation of style and expression comes to the conclusion that there is no evidence for a particular female language; however, this authoritative work is a joy to follow for anyone interested in language, linguistics, stylistic analysis, and gender.